A Matter to Think Over: Nativeness of English Teachers in Indonesia - Celya Intan Kharisma Putri (EDUPEDIA, 2021)
A shift is happening in languages used in Indonesia, especially in English as a foreign language that must be taught as a compulsory subject in Indonesian formal education institutions from primary to tertiary levels. English takes a place in the third position after Bahasa Indonesia and the regional languages. Since English as an International Language (EIL) paradigm appears, some debates burst up whether it is native speaker or non-native speaker teacher who should teach English in outer-expanding countries. This paper provides a discussion about the issue of native and non-native speaker of English related to the selection of English teachers in Indonesian context. The issue is analysed by using a list of teaching behaviours between native English speaker teachers (NESTs) and non-native of English speaker teachers (NNESTs) examined by Medgyes (1994). A few recommendations about the issue of selecting English teacher in outer-expanding countries are presented in the end of the paper.